Desafios da seguran??a do paciente na aten????o prim??ria ?? sa??de - Pierro, Luiz Marcelo Chiarotto (2020)
Patient safety is considered one of the dimensions of quality. Although there are many research in the hospital environment on patient safety, there are gaps in the knowledge of the culture of patient safety in primary health care. When considering that primary health care is estimated to have a resolution capacity of up to 80% of health problems, and that approximately 75% of the Brazilian population depends exclusively on public health, the study of patient safety culture in this scenario is carried out indicated. This research aimed to analyze the possibility of recognizing the culture of patient safety by professionals from basic health units in a city in the metropolitan region of S??o Paulo, according to a specific questionnaire, and to elaborate intervention criteria for improvements in the most fragile points as well as identifying the factors that most contribute to patient safety. The questionnaire was developed and applied in several countries, being translated and validated in Brazil. This is a survey of 23 Primary Care Units through a survey-type study, and using quantitative, descriptive methodology. We proceeded to assess all employees who had direct or indirect contact with patients. The Culture of Patient Safety has given rise to a new notion of safety in Primary Health Care, contributing to the improvement of health care and public health. The general perception of patient safety and quality of care was perceived by 51.8% of respondents. Working as a team, it was perceived by 85.52%, care monitoring 87.1%, organizational learning 80.1%, work Pressure and pace 72.9%. Communication on error 65.97%, open communication 64.87%, standardization of the process 62.75%, team training 48%, exchange of information with other institutions 37.3% Support and leadership 47.85%. Conclusion: It was identified that the culture of patient safety is adequate in the dimensions of patient safety in monitoring care, in organizational learning and in teamwork. In support and leadership, there was no perception of patient safety. In Pressure and work pace, standardization of processes, open communication, communication about error and exchange of information with other institutions, they do not present this perception, with the exchange of information with other institutions and training of the team with rates below 50%.